Ways to assess of seismicity of the territory of Syria - Alexander I. Dubyansky; Hiba Aljabasini (RUDN Journal of Engineering Research, 2019)
The article considers estimates of changes in the magnitudes of seismic events for two years (2005-2006) according to seismic catalogs. For this period, graphs of the law of repeatability of earthquakes were constructed and compared with each other. The analysis of the graphs of the frequency of occurrence of a number of zones built during seismic zoning was carried out, and the relationship between parameter A and the earthquake source mechanism was determined. Seismic zoning - the division of the territory into areas with varying degrees of intensity occurred and expected earthquakes. Seismic zoning data is used in the design and construction of earthquake-resistant structures and solving other practical problems in a seismically dangerous area. This is the applied aspect of seismic zoning. For the mapping of seismic zoning, historical data and instrumental observations of earthquakes, geological-tectonic and geophysical maps, as well as data on the movements of blocks of the earth’s crustare used. There are areas of possible occurrence of earthquake foci (OEF zones) with different depths. The greatest danger is represented by earthquakes with foci within the earth’s crust (at a depth of 3 to 30-50 km). The article provides a statistical analysis of the earthquakes of Syria for two years, taking into account historical earthquakes from the chronicles. The result of the work is the establishment of links between the identified earthquakes and the planetary events of the Earth, including solar activity. There is an increase in seismic activity in winter. Presented research should be used in forecasting future. It is worth noting that the basis for forecasting future natural events is the integration of analytical methods for analyzing data and theoretical ideas about the tectonics of the region in question.